Electrophysiological Correlates of Individual Differences in Perception of Audiovisual Temporal Asynchrony - Kaganovich, Natalya (Neuropsychologia, 2016)
Sensitivity to the temporal relationship between auditory and visual stimuli is key to efficient audiovisual integration. However, even adults vary greatly in their ability to detect audiovisual temporal asynchrony. What underlies this variability is currently unknown. We recorded event-related potentials (ERPs) while participants performed a simultaneity judgment task on a range of audiovisual (AV) and visual-auditory (VA) stimulus onset asynchronies (SOAs) and compared ERP responses in good and poor performers to the 200 ms SOA, which showed the largest individual variability in the number of synchronous perceptions. Analysis of ERPs to the VA200 stimulus yielded no significant results. However, those individuals who were more sensitive to the AV200 SOA had significantly more positive voltage between 210 and 270 ms following the sound onset. In a follow-up analysis, we showed that the mean voltage within this window predicted approximately 36% of variability in sensitivity to AV temporal asynchrony in a larger group of participants. The relationship between the ERP measure in the 210-270 ms window and accuracy on the simultaneity judgment task also held for two other AV SOAs with significant individual variability - 100 and 300 ms. Because the identified window was time-locked to the onset of sound in the AV stimulus, we conclude that sensitivity to AV temporal asynchrony is shaped to a large extent by the efficiency in the neural encoding of sound onsets.